145k views
4 votes
Which equation is y = 9x2 + 9x – 1 rewritten in vertex form?

User JacKeown
by
5.9k points

2 Answers

4 votes
y=(9x^2+9x)-1
y=9(x^2+x)-1
y=9(x^2+x+1/4-1/4)-1
y=9((x+1/2)^2-1/4)-1
y=9(x+1/2)^2-9/4-1
y=9(x+1/2)^2-13/4
User Ukasha
by
6.5k points
3 votes

Given equation :y = 9x^2 + 9x – 1.

We need to convert it in vertex form y= a(x-h)^2 +k

In order to find the vertex form, we need to find the values of a, h and k.

a is the coefficient of x^2.

Therefore, a = 9.

Now, we need to find the value of h.

h = -b/2a = -9/2(9) = -1/2.

Plugging x=-1/2 in given equation, we get

y = 9(-1/2)^2 +9(-1/2) -1.

y = 9/4 -9/2 -1

y = 9/4 -18/4 - 4/4

y = -13/4

We got h=-1/2 and k= -13/4.

Therefore, vertex form is


y = 9(x+(1)/(2)) ^2 -(13)/(4).

User Darwen
by
5.8k points